Light duty vehicle transportation and global climate policy: The importance of electric drive vehicles - Valentina Bosetti; Thomas Longden (Fondazione Eni Enrico Mattei (FEEM), 2012)
With a focus on establishing whether climate targets can be met under different personal transport scenarios we introduce a transport sector representing the use and profile of light domestic vehicles (LDVs) into the integrated assessment model WITCH. In doing so we develop long term projections of light domestic vehicle use and define potential synergies between innovation in the transportation sector and the energy sector. By modelling the demand for LDVs, the use of fuels, and the types of vehicles introduced we can analyse the potential impacts on the whole economy. We find that with large increases in the use of vehicles in many regions around the globe, the electrification of LDVs is important in achieving cost effective climate targets and minimising the impact of transportation on other sectors of the economy.
Keywords: Q54; R41; O3; 330; Light Duty Vehicles; Transportation; Climate Change Policy; Electric Drive Vehicles; Research and Development